The Degrees of Regular Polytopes of Type [4, 4, 4] - Fernandes, Maria Elisa (2022)
We give a list of all possible degrees of faithful transitive permutation representations, corresponding to the indexes of core-free subgroups, of the finite universal regular polytopes {{4,4} (t1,t2), {4,4}(s1,s2)}